2012
DOI: 10.1121/1.3687448
|View full text |Cite
|
Sign up to set email alerts
|

Rapid head-related transfer function adaptation using a virtual auditory environment

Abstract: The paper reports on the ability of people to rapidly adapt in localizing virtual sound sources in both azimuth and elevation when listening to sounds synthesized using non-individualized head-related transfer functions (HRTFs). Participants were placed within an audio-kinesthetic Virtual Auditory Environment (VAE) platform that allows association of the physical position of a virtual sound source with an alternate set of acoustic spectral cues through the use of a tracked physical ball manipulated by the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 32 publications
8
106
2
Order By: Relevance
“…The possibility that other sensorimotor mechanisms maybe involved in the accommodation to altered spectral cues was raised when these observations were first made (Hofman et al 1998). Prior to the current experiment, however, there have been no studies that have explicitly looked at the capacity to accommodate to new spectral cues for locations outside the visual field, let alone to the possible role of sensorimotor mechanisms in this process (see however, Zahorik et al 2006;Parseihian and Katz 2012). In this study, we have shown that the extent of accommodation (Fig.…”
Section: Accommodation To the New Spectral Cuesmentioning
confidence: 61%
“…The possibility that other sensorimotor mechanisms maybe involved in the accommodation to altered spectral cues was raised when these observations were first made (Hofman et al 1998). Prior to the current experiment, however, there have been no studies that have explicitly looked at the capacity to accommodate to new spectral cues for locations outside the visual field, let alone to the possible role of sensorimotor mechanisms in this process (see however, Zahorik et al 2006;Parseihian and Katz 2012). In this study, we have shown that the extent of accommodation (Fig.…”
Section: Accommodation To the New Spectral Cuesmentioning
confidence: 61%
“…Most of the subjects reached the same level of localisation performance as their counterparts from the control group (who listened to 3D sounds filtered with individualised HRTFs) after performing several training sessions (Parseihian, Katz, 2012;Blum et al, 2004). Moreover, the training procedure proved to have long-term effects, as the listeners recorded similar levels of performance even one month after the experiment had taken place (Honda et al, 2007).…”
Section: Training Sound Localisationmentioning
confidence: 96%
“…The sound localication cues contained in the HRTF spectrum are related with the lateralisation of the source and with elevation discrimination (Parseihian, Katz, 2012). As in the literature the term "lateralisation" has been used to describe the identification of virtual sound sources rendered over headphones, in this study we will use the term "localisation" to indicate the discrimination of target sound sources in virtual auditory displays.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations